Análisis de la pobreza y la fertilidad en el Ecuador, período 2020. - Maliza Chávez, Nelly Shirley (2023)
The objective of the current research work is to analyze and assess the relationship between poverty and fertility in Ecuador during the year 2020. This relationship is studied through the application of a logit model estimated with the Wald forward stepwise method, and which measurement instrument was the statistical registry survey of live births and fetal deaths for the year 2020. The results show that fertility has a positive and significant impact on poverty: the greater the number of children, the greater the probability of falling into poverty. In addition, when fertility is analyzed in terms of other conditions, such as the mother's low level of schooling, type of ethnicity and area of residence, there is more scope for explaining poverty rates.